Association of raised levels of IL‐4 and anti‐TPO with hyperprolactinemia. (30th January 2019) - Kalsi, Amanpreet Kaur; Halder, Ashutosh; Jain, Manish; Chaturvedi, Pradeep K.; Mathew, Mary; Sharma, Jai Bhagwan
Abstract : Background and objective: The modulatory role of prolactin in autoimmune regulation is well established. Hyperprolactinemia is often associated with autoimmune disease like systemic lupus erythematosus and autoimmune thyroid diseases. The objective was to compare levels of direct and indirect autoimmune factors in different categories of hyperprolactinemia cases and predict the direction of association between hyperprolactinemia and autoimmune factors, if any. Methods: A total of 102 hyperprolactinemia cases (>100 ng/mL serum prolactin level) were included along with 24 controls. Among 102 hyperprolactinemia cases, there were 36 idiopathic cases, 19 pituitary adenoma cases, 36 drug‐induced cases, and 11 cases associated with other secondary/systemic diseases (chronic renal failure, chronic hepatic failure, etc). Measurements: Direct autoimmune markers, IL‐2, IFN‐γ, IL‐4, and IL‐5, were measured in serum by ELISA. Indirect autoimmune markers, anti‐TPO, anti‐tg, anti‐CCP, VDRL, platelet count, and aPTT, were measured as per laboratory‐defined protocol. Results: Serum levels of IL‐4 and anti‐TPO were significantly high in idiopathic hyperprolactinemia cases. Serum IL‐4 levels were also significantly high in pituitary adenoma cases, drug‐induced cases, and in cases with other secondary causes of hyperprolactinemia. Serum anti‐TPO levels were also significantly high in drug‐induced hyperprolactinemia cases. Conclusion: No significant difference in autoimmune factors is observed between macroprolactinemia and true hyperprolactinemia. Serum IL‐4 and anti‐TPO were high in all categories of hyperprolactinemia. This suggests a possible association of hyperprolactinemia with autoimmune conditions (high IL‐4 and anti‐TPO), mostly subclinical. Thus, hyperprolactinemia case with serum prolactin level >100 ng/mL may require long‐term follow‐up for the development of autoimmune disease in future.